Discrimination of orientations in filled-in percepts compared with veridical ones - Ho, Ping Ghee (2018)
The optic disk is an area of the retina without photoreceptors, which cannot send signals of visual stimuli to the brain -- this area is the blind spot. When you place two identical Gabor stimuli, one in the blind spot and one in the actual visual field, humans are more likely to choose the stimuli in the blind spot as continuous - humans treat filled-in percepts that should be unreliable as more real than actual stimulation (Ehinger et al, 2017). The purpose of this study is to investigate if perceptual filling-in (Ramachandran, 1992) occurring in the physiological blind spot can allow people to form judgements on different orientations of Gabor stimuli, if they can perform differently from conventional, non-filled in percepts. Participants were presented one Gabor stimulus to each eye, placed overlapping their measured blind spots or outside of them, and asked to determine stimulus was more titled clockwise. They performed similarly whether the stimuli were placed overlapping the blind spot or outside of it. Filling-in led to a percept that was comparable to veridical percepts, and participants could determine orientation differences from filled-in perceptions similarly to how they would perceive real signals of visual stimuli.